2023
DOI: 10.1128/msphere.00019-23
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Shigella O-Polysaccharide–IpaB Conjugate Vaccine Elicits Robust Antibody Responses and Confers Protection against Multiple Shigella Serotypes

Abstract: Diarrhea caused by Shigella species results in long-term disability and mortality globally, disproportionally affecting younger children living in poor countries. Although it is treatable by antibiotics, the rapid and widespread emergence of resistant strains and the highly contagious nature of the disease compel the development of preventive tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…An unexpected finding was the low (negligible) VirGα-specific serum IgG responses in mice immunized IN with sublethal doses of S. flexneri 2a and S. sonnei (Fig. 2b ), while these controls developed robust serum IgG responses to the OPS of the respective immunizing strain 24 . VirGα-specific IgA responses were detected neither in serum or feces of mice immunized with VirGα via IM, nor in those that received sublethal IN doses of S. flexneri 2a and S. sonnei (data not shown).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…An unexpected finding was the low (negligible) VirGα-specific serum IgG responses in mice immunized IN with sublethal doses of S. flexneri 2a and S. sonnei (Fig. 2b ), while these controls developed robust serum IgG responses to the OPS of the respective immunizing strain 24 . VirGα-specific IgA responses were detected neither in serum or feces of mice immunized with VirGα via IM, nor in those that received sublethal IN doses of S. flexneri 2a and S. sonnei (data not shown).…”
Section: Resultsmentioning
confidence: 96%
“…A polyvalent fusion protein containing epitopes from IpaB, IpaD, VirG, GuaB and Shiga toxins has been shown to elicit broadly functional antibodies and cross-protection against S. sonnei and S. flexneri serotypes 27 . Our group developed a Shigella OPS-IpaB conjugate vaccine candidate capable of eliciting cross-protective immunity in mice 24 . IpaB and VirG are appealing vaccine targets because of their immunogenic properties and association with protective immunity in humans 43 , 44 , 58 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Shigella -infected Swedish patients reported that anti-LPS and anti-Ipa immunoglobulin G (IgG) responses are good indicators of recent and previous infections, respectively [ 7 ]. Invasion plasmid B (IpaB) appears to be a particularly well-conserved and immunogenic antigen, and antibodies to IpaB are a potential correlate of protection [ 8 , 9 ]. An association between higher levels of IgG1 antibodies with previous exposure to Shigella and lower risk of developing symptomatic infection was shown in a study conducted in the Israeli Defense Force using the double antibody sandwich enzyme-linked immunosorbent assay (ELISA) [ 10 ].…”
Section: Natural Immunity To Shigella Infectio...mentioning
confidence: 99%